Prodrug design : perspectives, approaches and applications in medicinal chemistry - Redasani, Vivekkumar K.; Bari, Sanjay B. (Academic Press is an imprint of Elsevier, 2015)
Prodrug Design: Perspectives, Approaches and Applications in Medicinal Chemistry provides a focused overview of this critical area of drug discovery, as that continuous process strives not only to discover new drug compounds but also to modify the existing ones. This valuable primer supports this mission of drug development and its goal of reducing undesired effects and improving therapeutic effectiveness of drug compounds. Providing a unique compilation of data, insightful case studies, and review of existing literature in the area, the book will promote innovation in medicinal and pharmaceu.